Analisis Investasi Pengembangan Bandar Udara Mutiara Sis Aljufri Palu - Labaso, Eko Rakhmat (Jurusan Teknik Sipil Universitas Tadulako, 2017)
Central Sulawesi is one of the six locations which determined as the economic growth corridor. It shows that infrastructure development is the main priority of this province. Mutiara SIS Aljufri Airport Palu is one of the several developed infrastructure in this region. The reason for this, the existency of transportation services is positively correlated to the economic and community development. Therefore, the government of Palu and the management of Mutiara SIS Aljufri Airport Palu agreed to improve the level of Mutiara SIS Aljufri Airport Palu as an international airport. This study aims to determine the developing investment of Mutiara Airport SIS Aljufri Palu. In addition, this study apply several analysis methods, such as, NPV, IRR and Profitability Index (PI) method. The result shows that the investment in the Mutiara SIS Aljufri Airport Palu is feasible based on the method of Net Present Value (NPV), Internal Rate of Return (IRR) and Profitability Index (PI) analysis.This investmental so provides enhanced services for users and air transport service providers. Based on the Gross Domestic Product (GDP) at constant 2000 prices in Quarter III (2014), the economic growth of Central Sulawesi Province increase compare to the the same quarter in previous year (2013). The proportion of economic growth is 6.58 % (y-on-y).